2009
DOI: 10.1001/archoto.2009.168
|View full text |Cite
|
Sign up to set email alerts
|

Complications That Affect Postlaryngectomy Voice Restoration

Abstract: Voice prosthesis complications are more frequently encountered in those who require salvage laryngectomy. Understanding the potential for such complications reinforces the need for close communication and follow-up with these patients by the speech language pathologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…These results support those of other investigators who have found that extended laryngectomy is strongly associated with TEP complications. (27, 29) In our cohort, hypopharyngeal tumors and laryngopharyngectomy were significantly associated with enlarged TEP as well as the three significant risk factors identified in the multivariable model. Cross-tabulations indicated that postoperative stricture (p=0.003) and advanced N-stage (p<0.001) were significantly more common in patients with hypopharyngeal disease, and recurrence after laryngectomy was significantly more common in patients who underwent laryngopharyngectomy (p=0.007).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These results support those of other investigators who have found that extended laryngectomy is strongly associated with TEP complications. (27, 29) In our cohort, hypopharyngeal tumors and laryngopharyngectomy were significantly associated with enlarged TEP as well as the three significant risk factors identified in the multivariable model. Cross-tabulations indicated that postoperative stricture (p=0.003) and advanced N-stage (p<0.001) were significantly more common in patients with hypopharyngeal disease, and recurrence after laryngectomy was significantly more common in patients who underwent laryngopharyngectomy (p=0.007).…”
Section: Discussionmentioning
confidence: 60%
“…The risk of enlarged TEP was highest in patients who received postoperative RT. This was unexpected, as current literature (7, 27, 28) finds elevated complication rates in salvage laryngectomy cases in whom definitive radiotherapy doses are traditionally higher than postoperative doses. Our finding, however, may be better explained by the difference in fields targeted for definitive versus postoperative radiation delivery as opposed to differences in dose.…”
Section: Discussionmentioning
confidence: 97%
“…The rate of TEP‐related complications was reported to be higher in those who had undergone radiation or chemoradiation previously by Starmer et al In their analysis, adjuvant treatment was associated with significantly increased risk of leakage around the prosthesis, prosthesis dislodgement, and size changes. Moon et al, however, found no significant difference in TEP‐related complications between those who had undergone primary versus salvage total laryngectomy with or without pharyngeal reconstruction.…”
Section: Discussionmentioning
confidence: 92%
“…The combined effects of chemoradiation and surgery mean that postoperative complications are common and may delay speech and swallowing rehabilitation . Moreover, individuals who undergo complex surgical reconstruction may be poor candidates for a tracheoesophageal prosthesis (TEP) for the voice and may be at risk for more negative long‐term communication and associated problems …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation